2020
DOI: 10.1177/0960327120901571
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity effects of Nerium oleander, basic and clinical evidence: A comprehensive review

Abstract: Introduction: Nerium oleander is a plant that is frequently grown in gardens and public areas. N. oleander is distributed originally in subtropical Asia but is now growing in many parts of the world, such as the United States, Australia, China, and Middle East countries. Pharmacological effects of plant including antinociceptive, anti-inflammatory, and anticancer activity were reported, but the potential toxic effects of all parts of the shrub either fresh or dried on animal and human body were documented. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…However, all the pharmacological interventions associated with Oleander are preclinical because of its toxicity profile. Indeed, several studies have demonstrated the lethal effects of oleander on animals and humans (Farkhondeh, Kianmehr, Kazemi, Samarghandian, & Khazdair, 2020).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…However, all the pharmacological interventions associated with Oleander are preclinical because of its toxicity profile. Indeed, several studies have demonstrated the lethal effects of oleander on animals and humans (Farkhondeh, Kianmehr, Kazemi, Samarghandian, & Khazdair, 2020).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…The quality and quantity of toxic compounds present in plant tissues are very important for the consequences on human health as well as the frequency of consumption. Some inedible flowers contain phytotoxins that can cause serious pathological conditions even if the consumer has eaten small amounts (e.g., Colchicum autumnale, Datura stramonium, Nerium oleander) [121][122][123]. Most of these plants produce floral nectar consisting of sugars (about 90% by dry weight) and several compounds, including lipids, amino acids, minerals, antioxidants, and secondary phytotoxic compounds transported between plant tissues via the phloem.…”
Section: Potential Toxic Compounds In Edible Flowersmentioning
confidence: 99%
“…2013), and anti‐inflammatory (Farkhondeh et al . 2020). N. oleander L. toxicity is well‐documented, and several studies have been reported in experimental animals.…”
Section: Introductionmentioning
confidence: 99%
“…The cardiac glycoside of N. oleander L. leaf extracts, cardenolides, were suggested as the causative toxic effects (Farkhondeh et al . 2020). Some of these cardenolides showed significant cytotoxicity against different cancer cell lines (Cao et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation